2017
DOI: 10.11591/eecsi.v4.1082
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of IPv6 Jumbogram Packets Transmission using Jumbo Frames

Abstract: IPv6 is an ultimate solution to the Internet address exhaustion. It is believed, the protocol will be requested by not only human but also everything on the earth surface. Furthermore, the improvement on the protocol is important to achieve IP packets transmission efficiently. Processing technology has been improved to become very fast packet processing both in host as well as intermediate systems. The lower layer technologies have supported to transmit Gigabits data per second. However, there is a limitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The widely used technology which is Ethernet is still standardized to use frame size 1518 bytes due to the MTU (maximum transmission unit) is 1500 bytes by default. The Gigabit Ethernet generation has been developed to provide large MTU, but the default is still 1500 bytes (Supriyanto, Sofhan, Fahrizal, & Osman, 2017).…”
Section: Xg-pon Jumbo Framementioning
confidence: 99%
“…The widely used technology which is Ethernet is still standardized to use frame size 1518 bytes due to the MTU (maximum transmission unit) is 1500 bytes by default. The Gigabit Ethernet generation has been developed to provide large MTU, but the default is still 1500 bytes (Supriyanto, Sofhan, Fahrizal, & Osman, 2017).…”
Section: Xg-pon Jumbo Framementioning
confidence: 99%
“…A number of previous research such as [16,17], [20][21][22][23][24][25], tried to increase the MTU by introducing jumbo frame as well as super jumbo frame. Shaneel Narayan and Paula Raymond [16] implemented jumbo frame on a test-bed infrastructure with computers installed using Windows Server 2003/2008 operating system.…”
mentioning
confidence: 99%
“…However, the papers did not consider the performance of the OS used. Experiments on transmitting large packets size as well as large frame size on windows OS was conducted in [24]. Results of the experiment showed that larger packet is able to reduce the network latency as well as increases the throughput of the network.…”
mentioning
confidence: 99%